MAIN THEMES OF THE NOVEL “SILVER DAGGER” BY SADETTINE JANPOLAT - Marem A. Yalkharoeva (Izvestiâ Ûžnogo Federalʹnogo Universiteta: Filologičeskie Nauki, 2024)
Rostov-on-Don Russian – in 2020, the second edition – in 2022 and is being investigated for the first time, the article is devoted to the novel "Silver Dagger" by Sadettin Janpolat/Dzaurov, which was published in Turkish in 2016 in Istanbul, in Russian - in 2020 in Rostov-onDon. The paper examines the main motives of the novel. These are the motives of the road and search; motives and images of national culture, national character; motives of love, friendship and brotherhood. The main one is the image of the road, which should help the heroes of the novel to find a way out of the difficult situation in which their people found themselves.